Business Process Reengineering: A Holistic Approach - Tehraninasr, Ali; Darani, Edris Heidari (2009)
The goal of this study is to have an overview on the subject of business process reengineering (BPR) with the emphasis on a holistic approach. First an introduction is presented containing a brief history of BPR from the time of the first sparkle flamed by Michael Hammer and then some standard and widely accepted definition of BPR are given. This is followed by a discussion which highlights some important features of reengineering with emphasis on a holistic approach.